First high resolution study of the pentad bending bands of deuterated silane: Energy structure of the (0200), (0101) and (0002) vibrational states of 28SiD4, 29SiD4 and 30SiD4; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 273 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Kuznetsov A. V. Aleksey Valerjevich; Leroy C. A. Claude; Sydow Ch. Christian; Bauerekker Z. Zigurd (2021, 2021)
Title screen